Qualitative and Quantitative Analysis of Vitamins, Micro-Macro Nutrient Content and Physicochemical Characteristics of Surat Dibata Leaves (Macodes Petola) - Nur Asyiah Dalimunthe; Rizal Aziz; Dwika Karima Wardani; Angga Ade Sahfitra (Postgraduate, University of Mataram, 2025)
This research was conducted with the aim of determining the vitamin content, micro-macro nutrients, and physicochemical properties contained in the leaves of the Surat Dibata plant (Macodes petola). The analysis procedure included qualitative and quantitative vitamin tests using the DCPIP method and UV-Vis spectrophotometry, analysis of micro-macro nutrients using AAS, and measurement of water content, ash, pH, and water-soluble organic compounds based on the AOAC standard method. The test results showed that qualitatively these leaves contain vitamins C, B1, and E, with concentrations (mg/100 g) of 47.8; 1.02; and 0.99, respectively. Meanwhile, for micro-macro nutrients such as Fe, Zn, Mg, and Ca, quantitative results showed levels (mg/kg) of 47.2; 30.7; 212.3; and 433.7, respectively. Furthermore, the detected water content was 79.22%, the ash content was 10.15%, the pH was 5.8, and the water-soluble organic compound content reached 66.6%. Overall, this data shows that Surat Dibata leaves have great potential as a natural source of nutrients and phytochemicals that support the development of herbal products and environmentally friendly agriculture.